Effect of Natural Aging on Oak Wood Fire Resistance - Zachar, Martin; Čabalová, Iveta; Kačíková, Danica; Jurczyková, Tereza (Polymers, 2021)
The paper deals with the assessment of the age of oak wood (0, 10, 40, 80 and 120 years) on its fire resistance. Chemical composition of wood (extractives, cellulose, holocellulose, lignin) was determined by wet chemistry methods and elementary analysis was performed according to ISO standards. From the fire-technical properties, the flame ignition and the spontaneous ignition temperature (including calculated activation energy) and mass burning rate were evaluated. The lignin content does not change, the content of extractives and cellulose is higher and the content of holocellulose decreases with the higher age of wood. The elementary analysis shows the lowest proportion content of nitrogen, sulfur, phosphor and the highest content of carbon in the oldest wood. Values of flame ignition and spontaneous ignition temperature for individual samples were very similar. The activation energy ranged from 42.4 kJ·mol-1 (120-year-old) to 50.7 kJ·mol-1 (40-year-old), and the burning rate varied from 0.2992%·s-1 (80-year-old) to 0.4965%·s-1 (10-year-old). The difference among the values of spontaneous ignition activation energy is clear evidence of higher resistance to initiation of older wood (40- and 80-year-old) in comparison with the younger oak wood (0- and 10-year-old). The oldest sample is the least thermally resistant due to the different chemical composition compared to the younger wood.
Keywords: chemical composition; historical wood; spontaneous ignition temperature; mass burning rate; oak wood; activation energy; flame ignition temperature